Efektivitas Relaksasi Napas dalam Terhadap Nyeri Pada Pasien Pasca Operasi Orif Fraktur Ekstremitas Bawah di RS Karya Medika - Chotimah, Chusnul; Sahrudi, Sahrudi; Simanjuntak, Sondang Mery Wati (Universitas Malahayati, 2025)
ABSTRACT A fracture is an unexpected event that causes a fracture or loss of bone continuity, that is, cartilage, either wholly or partially caused by physical trauma, which causes psychological and physiological disorders that cause painful effects. The treatment of fracture patients can be done with surgical procedures, namely surgery is carried out by open reduction with internal fixation (Orif: Open Reduction Internal Fixation). After undergoing the surgery process, the side effect that often appears is pain. The pain caused by surgery makes the patient feel uncomfortable and complains of pain. This research was carried out because of the existence of effective non-pharmacological treatments to help reduce pain intensity. The Deep Breath Relaxation Technique is a method that is carried out when the patient feels pain in the form of a series of breathing exercises that can reduce oxygen consumption, lower breathing rate, reduce heart frequency and muscle tension. Purpose to determine the effect of the effectiveness of deep breath relaxation on pain in postoperative patients with lower extremitis fracture orif. The type of research used is quantitative research and the design used is